Seeking new meaning and the effectiveness of reception: A reading of "Al-Sina’atayn" by Abu Hassan Al-Askari (395 AH) - Rashid, Ass. Prof. Adnan Mashal (Thi Qar Arts Journal, 2023)
The meaning is the soul of the language and the basis of its creativity, it occupies a wide position in the process of systems, the critics gave it their attention for its importance, as they did not care about anything as much as they cared about it, through their setting of technical standards that they subjected to it, they wanted through it to reach the ideal meaning, as the meaning was not good for them unless it was evaluated by quality standards and included under it, and often the old Arabic poetry was characterized by possessing the good and ideal meaning, due to the skill of the poets, their brilliance and their mastery of the artistic craft in their production.